Impact of psychology, financial resources, economic forces and investor involvement on retirement investor decision behaviour - Santhana Rajan, Marcia Edna (2020)
In Malaysia, the greatest majority of private sector employees, who are the Employees Provident Fund (EPF) contributors rely heavily on savings accumulated with the EPF as the only significant retirement plan, but to-date most are unprepared. While the EPF's Members' Investment Schemes (MIS) endeavoured to relax this setback through the formation of individual investor responsibility on investing part EPF retirement savings into unit trusts, still a negligible fraction of these individuals have been documented to leverage on this decision notwithstanding long-term growth and profitability in the unit trust industry, outperforming even yearly EPF dividends. Henceforth, this thesis makes enquiries into the individual retirement investor decision behaviour of Malaysian EPF contributors and the factors that form pushes and pulls in influencing this criterion. In doing so, the current investigation estimates an integrated framework examining the impact of an array of psychological factors, in addition to financial resource, economic force, and investor level of involvement influences on retirement investor decision behaviour - the deduction of which stem from four prominent models comprising Hershey's model, behavioural finance theory, life-cycle hypothesis, and social judgement theory. The study adopted a non-experimental, correlational causal design, using the Partial Least Squares-Structural Equation Modelling (PLS-SEM) technique to measure variables, test hypotheses, and determine the existence of cause-and-effect relationships between variables. To estimate the PLS-SEM, a questionnaire-based survey was employed to solicit responses from EPF contributors in listed private firms and private universities within the Klang Valley, Malaysia. Respondents were asked about their perceptions in exercising their retirement investor decision behaviour as EPF contributors, in which 214 questionnaires were successfully completed for use in the study's analysis. Results from the PLS-behaviour as EPF contributors, in which 214 questionnaires were successfully comp -SEM indicated that 7 of 15 hypotheses assessed tested significant. Among all factor dimensions, the larger fraction of significant relationships emerged from personality trait psychology. This is followed by cognitive psychology, economic force, and investor level of involvement factors. More importantly, most predictor variables proved valuable since these produced substantive significance towards the criterion. Several contributions and implications emerge from this study. For one, the development of a cohesive framework of a psychological dimension informing retirement investor decision behaviour. For Malaysia, results extend early homegrown findings, and are instrumental as current work in the field is limited, especially in the examination of psychological influences. Evidence on medical expense risk is valuable particularly since its exploration has yet to receive focus contextually and within Malaysia. Finally, results on investor involvement has also proven useful contextually, emerging the most influential factor, as well as enriching existing limited evidence in the financial context, particularly in the area of retirement financial planning and investment behavioural studies. In aggregate, the outcomes of this study should assist the EPF in policy making aimed at creating sustainable retirement income for its members, and to fund management institutions and financial advisors, to develop marketing strategies and provide advice for active retirement investor participation.